THE EPIDEMIOLOGICAL DETERMINATION OF NOSOCOMIAL INFECTION IN INPATIENTS AT ADAM MALIK GENERAL HOSPITAL, MEDAN - Sazkiah, Ema Rizka; Ismah, Zata (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Nosocomial infection is a complication that most often occurs in hospitals and other health services. Infection is a most widely acquired hospital effect that can affect 5 to 10% of all hospitalized patients in developed countries and in low-background countries being a major burden. Objectives: This study aims to determine the epidemiological determinants of nosocomial infections in inpatients at the General Hospital of the Haji Adam Malik Center, Medan in 2019.Method: Determination of the sample size in the case and control using unpaired categorical analitical formula obtained a total sampel of 90 patients with ratio of 1:1. Data analysis using chi-square test analysis. Result: The results showed that the dominant type of infection was urinary tract infection (35.6%), the most widely used type of invasive procedure was catheters (35.6%), the most common type of germs was conditional pathogens (84.4%), and the most common type of invasive procedure was catheter treatment ≥ 7 days (64.4%). The determinants of nosocomial infection in hospitalized patients were the type of invasive action (surgery, p value 0.013 and length of stay of patients (≥ 7 days, p value 0.035). Conclusion: Performing surgery in accordance with standart operational procedure, applying surgical site infection bundles, discharging surgery patients on the fourth day, improving personal hygiene, reducing invasivtione procedures and providing antimicrobials to patients are necessary to reduce the incidence of nosocomial infections.